Association between Personality Disorders and Uncontrolled Type 2 Diabetes Mellitus: A Case–Control Study - Rezaeisadrabadi, Dr. Mohammad (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: Type 2 diabetes mellitus (T2DM) is one of the most common chronic diseases, with a wide range of complications and comorbidities. Personality disorders can lead to more blood sugar fluctuations in these patients. This study aimed to determine the relationship between personality disorders and increasing the sugar level in T2DM. Methods: In this case–control study (March 2016–September 2017), the personality of two groups of patients with T2DM referred to Imam Hossain Hospital in Tehran, Iran, was assessed retrospectively. 36 patients with uncontrolled T2DM, as the case group, were compared with 108 patients with T2DM, who were hospitalized due to other reasons, as the control group. The Iranian short form of Minnesota Multiphasic Personality Inventory was used to distinguish personality disorders. The most prevalent personality disorders were hysteria (HY) and depression in the case group and HY and psychopathic deviancy in the control group. There were significant differences between the groups in most of the personality disorders. Results: Results of the logistic regression showed that the patients in the case group compared with those of the control group had psychasthenia 36.5-folds more (P < 0.0001), schizophrenia 30.3-folds more (P < 0.0001), depression 13-folds more (P < 0.0001), hypochondriasis 9.1-folds more (P < 0.0001), mania 7.3-folds more (P < 0.0001), and paranoia 3.7-folds more (P = 0.001). Conclusion: The prevalence of personality disorders was very high in adults with T2DM, which can lead to uncontrolled blood sugar (BS). It is suggested that physicians should try to manage and treat personality disorders to better control of BS.